2019
DOI: 10.1001/jamapediatrics.2019.3000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immersive Virtual Reality Education Before Chest Radiography on Anxiety and Distress Among Pediatric Patients

Abstract: IMPORTANCE Pediatric patients often encounter anxiety and distress in hospital settings, and virtual reality education, providing a vivid, immersive, and realistic experience, has been introduced to mitigate these anxiety responses.OBJECTIVE To evaluate whether virtual reality education for pediatric patients before chest radiography could reduce anxiety and distress in children and improve the radiographic process. DESIGN, SETTING, AND PARTICIPANTS This prospective randomized clinical trial was conducted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 12 publications
5
62
0
1
Order By: Relevance
“…This supports previous findings in the literature. Our previous study investigating pediatric patients who received VR prior to undergoing chest radiography showed that VR decreased the number of distressed patients from 48% to 22.4% [ 32 ]. Ganry et al [ 33 ] measured the salivary cortisol concentration, which is a biological marker of anxiety, in 20 patients scheduled for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This supports previous findings in the literature. Our previous study investigating pediatric patients who received VR prior to undergoing chest radiography showed that VR decreased the number of distressed patients from 48% to 22.4% [ 32 ]. Ganry et al [ 33 ] measured the salivary cortisol concentration, which is a biological marker of anxiety, in 20 patients scheduled for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Children in the tablet group experienced the process of chest radiography indirectly with a 3 min video using a tablet PC ( Figure 1 A). Children in the VR group, on the other hand, experienced the same content and information as the control group, but using a head-mounted VR display ( Figure 1 B), offering a 360°, 3-dimensional virtual environment that introduced and explained the process of chest radiography, which was described by Han et al [ 5 ]. In this VR content, the participant, along with Chatan and Ace, who are famous animation characters in the animated film Hello Carbot (Choi- Rock Contents Factory, Seoul, Republic of Korea), experienced the chest radiography together in the radiography room ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Pediatric patients usually suffer from anxiety and distress ahead of a procedure or surgery; the primary challenge of hospital staff is to reduce such anxiety and distress. Besides various interventions, such as premedication, parental presence and behavioral intervention [ 3 , 4 ], exposure therapy using video or VR is shown to be effective in controlling anxiety and distress among children before a procedure or surgery [ 5 , 6 , 7 , 8 ]. Exposure using video or VR allows the pediatric patients to confront the fearful or unknown situation by providing visual expectations ahead of the procedure, allowing the children to become familiar with the room and the overall process [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians, nurses, and families (including the patients) require relevant and trusted information delivered in an engaging, and developmentally and professionally appropriate way to support the rapid acquisition in knowledge [44,45]. Recent advances in medical education for patients and clinicians have focused on using immersive virtual and augmented reality (AR/VR), app-based interactive training, virtual assistants to answer questions in real-time, 3D modeling, and online real-time education [8,46,47]. In particular, virtual assistants or chatbots have been identified as a technology suitable for supporting patient groups with focused information available in real time [48][49][50].…”
Section: Principal Findingsmentioning
confidence: 99%